Climate - MDPI (MDPI, 2026)
Climate is a scientific, peer-reviewed, open access journal of climate science published online monthly by MDPI. The American Society of Adaptation Professionals (ASAP) is affiliated with Climate and its members receive discounts on the article processing charges.
Keywords: Climatología; Cambio climático; Revistas depredadoras; Predatory journals